Multifaceted roles of SUMO in DNA metabolism - Yee Mon Thu (Nucleus)
Sumoylation, a process in which SUMO (small ubiquitin like modifier) is conjugated to target proteins, emerges as a post-translational modification that mediates protein−protein interactions, protein complex assembly, and localization of target proteins. The coordinated actions of SUMO ligases, proteases, and SUMO-targeted ubiquitin ligases determine the net result of sumoylation. It is well established that sumoylation can somewhat promiscuously target proteins in groups as well as selectively target individual proteins. Through changing protein dynamics, sumoylation orchestrates multi-step processes in chromatin biology. Sumoylation influences various steps of mitosis, DNA replication, DNA damage repair, and pathways protecting chromosome integrity. This review highlights examples of SUMO-regulated nuclear processes to provide mechanistic views of sumoylation in DNA metabolism.